Effect of parental mutuality on the quality of life of mothers of children with special health needs - Paula Rossi Baldini; Bruna Josiane de Lima; Beatriz Helena Naddaf Camilo; Juliana Coelho Pina; Aline Cristiane Cavicchioli Okido (Universidade de São Paulo, 2021)
Objective: to analyze the effect of parental mutuality on the quality of life related to the health of mothers who care for children with special health needs. Method: an observational, analytical and cross-sectional study with a quantitative approach. The following instruments were applied to 181 caregiving mothers: The Medical Outcomes Study 36-Item Short Form and Family Management Measure (Parental Mutuality subscale). In the statistical analysis, Spearman's correlation and univariate and multivariate linear regression were used. Results: the total score of parental mutuality was 30.8, indicating a satisfactory perception of the caregiving mother about the way the couple shares decisions regarding the care of the child. In the multivariate regression analysis, parental mutuality maintained a statistically significant association with the domains of pain, social aspects and emotional limitations of quality of life related to health (p=<0.001, 0.003, 0.002), respectively. Conclusion: parental mutuality has a positive effect on some domains of quality of life related to health. It is recommended to plan actions aimed at strengthening the complicity and connection between the couple, especially in matters related to the care of the child with special health needs.